Handbook of microstrip antennas - James, James R.; Hall, P. S. (Peter S.). (London, U.K. P. Peregrinus on behalf of the Institution of Electrical Engineers, 1989)
This book presents a wide ranging coverage of principles, state-of-the-art design and up-to-date applications of microstrip antennas; Includes detailed explanations of a variety of analytical techniques from transmission line theory to moments methods and their applications to CAD; Covers the numerous patch designs and array configurations giving many examples of practical applications; Discusses microstrip technology in detail including substrates, processing and environmental aspects; Addresses measurement methods particular to printed antennas such as substrate and connector characterisation and near field probing; Application areas covered include antennas for satellite terrestrial and mobile communications, conformal and aerospace antennas, phased arrays, hyperthermia applicators and millimetric antennas.
Electronic reproduction.
Keywords: Microwave antennas; Microstrip antennas; Electronic books